Extreme Religious Ideology and Violence in Northeast Nigeria: The rise and rage of Boko-Haram - Uganden , Iveren Adoo; Akuraga, Fanen (Kashere Journal of Politics and International Relations, 2025)
Since Nigeria’s return to democratic rule in 1999, the country has experienced violence rooted in religious and ethnic causes resulting in significant human and material losses. This violence is largely fueled by the nation’s deep religious sensitivities, which have created an environment conducive to the rise of religious radicalism and fundamentalism. This paper examines the relationship between extreme religious ideology and violence in Nigeria’s North-east. Adopting an ex-post-facto research design and relying on secondary data sources, the study applies the Islamic Theocratic State Theory as its analytical framework. Findings reveal that religious ideologies have not only set a precedent for extremism but have also emboldened conservative Islamic groups in their attempts to impose a rigid interpretation of Islam on Nigeria’s secular state. This has led to widespread violence and destruction, causing immense suffering among the general population. The paper recommends that advocacy for a return to orthodox Islam, as championed by Boko Haram, should be pursued through peaceful preaching and persuasion rather than through violent means.